Visibility of Board-Certified Dermatologists on TikTok - Chaitra Subramanyam; Alyssa Becker; Julianne Rizzo; Najiba Afzal; Yvonne Nong; Raja Sivamani (JMIR Publications, 2024)
Tik Tok is an emerging social media platform that provides a novel opportunity for health practitioners such as dermatologists to disseminate accurate health information.